A Comparative study between Muhammad Iqbal’s and Robert Browning’s Concerns with free-will versus determinism within the contexts of aestheticism and ethics - Mohd Ramli, Aimillia (2012)
The great Muslim poet-philosopher Muhammad Iqbal was perhaps full of admiration for the Victorian poet Robert Browning when, in Reconstructions of Religious Thoughts in Islam, he mentions that that the later “turns the impossibility [of absolute knowledge] to ethical use by a very ingenious argument. The uncertainty of human knowledge, teaches the poet, is a necessary condition of moral growth; since complete knowledge will destroy the liberty of human choice.” Yet stark contrasts exist between the two men’s conception of “human choice” or free-will. This is partly because the attention to man’s struggles with his own Self in order to know the world and his active reaction to it in Browning’s poem is often bereft of any guiding principle, leading his protagonists sometimes to experience moral depravity and, at other times, disillusionment. Iqbal’s concept of Free-will, however, sees it as a divine gift that is to be used with balance, amongst other things, in order to serve Allah (S.W.T.). This paper argues that this provides a solution to traditional opposition between aestheticism and ethics, since for a character to assert his free-will does not ultimately mean he is essentially “immoral” and the literary work lacks aesthetic value.